Além da demografia: propostas de segmentação do mercado de vinhos finos - Giriboni, Pedro Pohlmann (2016)
Countless changes have been occurring in the wine world in the last century. The French Chateaux wine now competes with wines from multinational companies whose collaborators are technically and scientifically trained to produce the most diverse styles of wines. In this scenario, market should be segmented so that the marketing efforts of the wine industries haves real effects. Although demographic segmentation brings great collaborations to consumer understanding, other methodologies, such as lifestyle segmentation, taking into account consumer attitudes, interests and opinions, seem to yield better results. This work aims to synthesize and discuss researches that segment the wine market in different ways. A narrative bibliographic review was carried out between February and October 2016, taking into consideration works with beyonddemography proposals of segmentation. What is observed is that generally are consumers with a high degree of knowledge, consumers oriented by the image, consumers engaged in learning about drink and those attached to a brand or style of product for fear of committing what they consider "error ". There is a lot to be studied about the wine consumer in Brazil, a continental country with a huge cultural multiplicity, and this challenge, to get to know the Brazilian consumer, is just one – producing what these consumers want can be as challenging as understanding them.